Are anxiety levels associated with the decision to participate in a Swedish colorectal cancer screening programme? A nationwide cross-sectional study. Issue 12 (22nd December 2018) - Wangmar, Johanna; von Vogelsang, Ann-Christin; Hultcrantz, Rolf; Fritzell, Kaisa; Wengström, Yvonne; Jervaeus, Anna
Abstract : Objectives: Colorectal cancer (CRC) screening programmes are commonly challenged by low uptake, limiting their potential to reduce CRC burden. We aimed to investigate anxiety levels related to the decision to participate or not in CRC screening among screening participants and non-participants. Further to explore associations between higher anxiety levels related to the decision and individuals' characteristics. Design: A nationwide cross-sectional study conducted with individuals included in a national randomised controlled CRC screening trial, the Screening of Swedish Colons (SCREESCO). Participants: A total of 1409 individuals, 60–62 years, recruited from SCREESCO during 2015–2016 participated in the study; 1256 had participated in CRC screening (faecal immunochemical test: n=958; colonoscopy: n=298) and 153 had declined screening participation. Measures: Anxiety levels were assessed with the State-Trait Anxiety Inventory (STAI) S-Anxiety Scale. Health literacy (HL) was assessed with the Swedish Functional and Communicative and Critical Health Literacy Scales. Results: Altogether, 79% of survey participants reported lower anxiety levels regarding their CRC screening decision (STAI S-Anxiety <40). Anxiety levels did not differ between screening participants and non-participants (mean STAI S-Anxiety score=34.1 vs 33.9, p=0.859). The odds of reporting higher anxiety levels increased by female sex (OR=1.37; CI 1.04 to 1.80; p=0.025) and previous faecal sampling (OR=1.53; CI 1.14 to 2.05; p=0.004), and decreased if living with partner (OR=0.65; CI 0.48 to 0.88; p=0.005), working (OR=0.72; CI 0.53 to 0.96; p=0.027) or having sufficient HL (functional: OR=0.49; CI 0.33 to 0.73, p ≤ 0.001; communicative and critical: OR=0.55; CI 0.38 to 0.82; p=0.003). Conclusions: Anxiety levels did not differ between screening participants and non-participants. Higher anxiety scores were associated with certain characteristics. Interventions accounting for these characteristics can be applied to reduce anxiety and facilitate programme acceptance. Trial registration number: NCT02078804 ; Results.